Efektivitas Program Buka Puasa Prasmanan sebagai Strategi Peningkatan Penghimpunan Dana dan Loyalitas Muzaki di Lazismu Banyumas - Febi Awaliyah Pramesti; Aulia Najwa Faroha; Aqila Fatihatu Zahra; Mahardhika Cipta Raharja (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study is motivated by the importance of innovative social programs in increasing fundraising and donor loyalty within Islamic philanthropic institutions. The research aims to analyze the effectiveness of the buffet iftar program as a fundraising strategy and a means of strengthening donor loyalty at LAZISMU Banyumas. This study employed a descriptive qualitative approach through a literature study method supported by interview data, documentation of the 2025–2026 Ramadan reports, and social media observation. The findings indicate that the buffet iftar program was effective in increasing fundraising, strengthening institutional image, and enhancing public participation and trust. The success of the program was supported by the innovative buffet concept, digital fundraising strategies through social media, transparent fund management, and the involvement of various community elements. The research data show an increase in total fundraising from IDR 6.0 billion in 2025 to IDR 6.4 billion in 2026, along with an increase in the number of donors from 2,347 to 2,427 individuals. The program also succeeded in strengthening donor loyalty through social and spiritual experiences that fostered emotional connections between the community and the philanthropic institution.